Staged Ultrasound-Assisted Catheter-Directed Thrombolysis for Bilateral Pulmonary Embolism: "All with one Catheter-Technique" - Tareq Ibrahim; Michael Dommasch; Moritz Wildgruber; Karl Ludwig Laugwitz (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
A 70-year-old male presented with two days increasing dyspnea. His past medical history was notable for deep venous thrombosis with consecutive pulmonary embolism (PE). Diagnostic workup showed normal blood pressure (130/80mmHg), sinus tachycardia with SIQIII-pattern on electrocardiogram, and elevation of thrombolysis-catheter with a staged infusion protocol since the patient was hemodynamically stable. For this purpose, an ultrasound assisted catheter (EkoSonic MACH4e Endovascular System, EKOS Corporation, Bothwell, WA) was positioned into the left lower PA-branch via the right femoral vein and rtPA-thrombolysis was administered over 16h (0.8mg/hour) until the next morning. On the next day, a second venous access was placed into the left femoral vein and with the help of a 6F-right-amplatz-catheter, the thrombolysis troponin (0.22ng/nl). Immediate chest computed tomography (CT) demonstrated PE in both pulmonary arteries (PA) and right ventricular (RV) dilation compatible with PE of intermediate-high risk for early mortality (Figure 1).